Methods of organization of cognitive activity of pupils in biology lessons - Zhumagaliyeva, Zh.Zh.; Eleupaeva, Sh.K.; Chernik, B.P. (Fundamental and Experimental Biology, 2019)
Contemporary and effective pedagogical technologies used in the work of general educational institution are considered in the article. Relevance of the use of contemporary innovational technologies in the action of general educational institution is justified. The article is devoted to the issue of using new innovational technologies. According to the use of technologies in the process of general educational institution attention is paid to the direction of possibility to projecting of educational process on the basis of pedagogical technology, effective use of new methods and forms of organizing the study, motivating of the pupils to cognitive action, increase of their activity, full mastering of given educational material. The use of new innovational technologies in educational process is one of the important feature of developing and modernizing educational process. New methods give the possibility to the cognitive function of pupils to be active; provide motivation for study; provide high level of analyzing exercises; improve knowledge, skills and observation. Effective-ness of using new innovational methods is related to electronic resources, usage of ways and objects of these technologies, corresponding to working methodology of the teacher. Developmental level indicators of emotional-motivational and cognitive components in forming biological knowledge of the pupils were defined and the review on the results of pedagogical experiment was made.